Coral Cay Conservation Coastal Community a marine expedition base in Mabini, Batangas - Cruz, Ma. Trisha Alyssa A.
The Coral Cay Conservation Coastal Community serves not only the purpose of marine conservation in the Philippines, but also, and somewhat more importantly, as a long-standing advocacy for environmental protection, demonstrating how architecture can put harmony between nature and humans. It sought to employ low environmental impact design, coupled with tropical, passive and resilient design on the design and construction of a centralized learning environment. The thesis project's aim were to exemplify integrity and mutualism through architecture with the use of different strategies, construction methods and materials, in order to aid future projects that are to be developed in coastal settings.